Effect of Temperature and Humidity on Oil Quality of Harvested Torreya grandis cv. Merrillii Nuts During the After-Ripening Stage - Zhang, Zuying; Jin, Hangbiao; Suo, Jinwei; Yu, Weiyu; Zhou, Minyin; Dai, Wensheng; Song, Lili; Hu, Yuanyuan; Wu, Jiasheng (Frontiers in Plant Science, 2020)
Temperature and relative humidity (RH) influence post-harvest ripening, a crucial stage for quality promotion in some oil plants or fruits. Torreya grandis cv. Merrillii nuts, which are rich in unsaturated fatty acids (UFA), are easily affected by temperature and humidity, and they oxidize quickly during the post-harvest ripening stage, leading to the deterioration of nut quality. In this study, the main nutraceutical components, fatty acid composition, and related metabolic parameters of lipid rancidity under four treatments (20°C and 70% RH, T20-LH; 30°C and 70% RH, T30-LH; 20°C and 90% RH, T20-HH; 30°C and 90% RH, T30-HH) were measured. The post-harvest ripening process was advanced under HH treatments (T20-HH and T30-HH) compared to LH treatments (T20-LH and T30-LH) and was associated with a shorter time for the seed coat to turn dark black and a faster reduction in starch content. The amount of unsaturated fatty acids significantly increased under the T20-HH treatment, but significantly decreased under the T30-HH treatment from 12 to 16 d of ripening time. The acid value (AV) and lipase activity under the T30-HH treatment remained virtually constant from 12 to 16 d of ripening time, and this was accompanied by a dramatic increase in peroxide value (POV), lipoxygenase (LOX) activity, and relative expression of the LOX2 gene. Meanwhile, a significant positive correlation between LOX activity and POV, malondialdehyde (MDA) content, and O2⋅– content was observed. The results imply that the lower amount of oxidative rancidity induced by the T20-HH treatment is related to the LOX activity induced by down-regulation of the LOX2 gene during the late after-ripening stage. Therefore, the T20-HH treatment not only promoted the post-harvest process of T. grandis ‘Merrillii’ nuts but also delayed lipid oxidation, which was ultimately associated with better oil quality at the late after-ripening stage.